Pengaruh Fasilitas Kerja terhadap Kinerja Karyawan Panen Kelapa Sawit di Kebun Mayang PTPN IV - Rico Rapa Rendy; Tifany Zia Aznur; Delyana Rahmawany Pulungan (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to determine the effect of work facilities on the performance of oil palm harvesting employees at PT Perkebunan Nusantara IV Kebun Mayang. This study uses a quantitative descriptive method. Data were obtained through observation, interviews, documentation, and distribution of questionnaires to harvesting employees. The study population was 116 people with a sample of 54 respondents determined using probability sampling techniques with a simple random sampling method. Data analysis was carried out using validity tests, reliability tests, simple linear regression analysis, partial tests (t-tests), and coefficients of determination (R²). The results showed that work facilities had a positive and significant effect on the performance of harvesting employees. The simple linear regression equation obtained was Y = 2.213 + 0.892X. The results of the partial test showed a calculated t value of 12.755 greater than the t table of 2.006 with a significance level of 0.000 <0.05. The coefficient of determination (R²) of 0.758 indicates that work facilities have a 75.8% influence on harvest employee performance, while the remaining 24.2% is influenced by other factors outside the study. Therefore, the better the work facilities provided by the company, the greater the performance of harvest employees in achieving the company's production targets.